THE IMPERISATION OF THE EUROPEAN UNION AND THE SMALL STATES - Brunalas, Benas (Politologija, 2015)
In this article by applying the ideas of M. Foucault, E. Said, A. Negri, M. Hardt, L. Wittgenstein, Z. Norkus, N. Statkus, R. Lopata, N. Luhmann and others, the model of the EU imperialism is introduced. By using the theory of family resemblance by L. Wittgenstein and logic of its employment as shown by Z. Norkus in his work on Grand Duchy of Lithuanian as the empire, the conclusion arrives that the EU gravitates from the classical or neo-classical definition of the empire. However, inaccuracies, found by applying Z. Norkus’ methodology, are caused more by the form, and not by the content, thus the claim that EU holds the notion of the empire is valid. This allows entitling the EU as the post-modern empire. In this work the main focus is set on the ruling regime of the post-modern empire of EU and on the main centre, which subordinates the other centres – “the core”. It is the main centre of the empire of EU. The core is not visual (European Commission, Court of Justice of the European Union are just the parts of “the core”.) It is more of a governing strategy, the entirety of values, standards, texts and rules that are imposed onto other centres. Two time-periods are highlighted: the first one is the expansionist experience of the Europe in 16th–20th centuries, when the justification of the EU as a civilizing force emerges (legitimate expansionism of the governing of the EU); the second is the time-period from the end of 20th century, since when the sensation that only the law, standards and virtues of the EU outtops the preferences of the national state, arises. That last momentum determines the equality of all the member-states, even though the asymmetry of force is clearly visible. The capability to subordinate the national preferences for the values and strategies of “the core” determines the success or the failure of the national politics. On this account, the influence of the small states in the EU is immediately concerned with the level of its integration and the ability to assimilate the standards and virtues, as postulated by “the core”. The more the state integrates and the more of the sovereignty it renounces, the more leverage it acquires. Accordingly, the asymmetry of force between the large and small states decreases. As the conclusion that the renouncement of sovereignty ensures more of the force, arises, the Lithuanian claim for regional leadership is proposed through the better integration and renouncement (delegation) of sovereignty.